Lack of Alternative Leadership in Democratic Malawi: Some Reflections Ahead of the 2004 General Elections (Nordic Journal of African Studies, 2003)
This article, drawing on Malawi's experience with intra party politics, argues that quality, dynamic and visionary leadership is extremely vital in propping up budding democracies on the winding road to mature democracies. It is thus widely recognized that the success or failure of any organized group effort whether at organizational, community or national level is critically dependent on leadership understood as a collective endeavour within a permissive and enabling framework. The major problem in most democratizing polities, however, is that leadership is essentially understood as rulership. This implies that leaders make every effort to ensure that decisions must either be made or reviewed at a single, known, predetermined and consistent position. Unless leaders extricate themselves from the perils of the centrist tendencies and work to facilitate participative governance in which they primarily serve as agents or trustees for a broad community of persons, democratizing polities risk disintegrating into dysfunctional political entities along the way.